An electronic ballast with wide dimming range, high PF, and low EMI. - Hui, S.Y.R (IEEE Transactions on power electronics)
The authors describe an electronic ballast design with the capability of low radiated and conducted EMI over a wide dimming range. It overcomes some limitations of traditional electronic ballasts that use frequency variation for dimming control. The proposed design allows soft switching of the ballast from full-power operation down to less than 10% power. Low-cost and low-voltage power metal oxide semiconductor field effect transmitters (MOSFETs) can be used in the proposed dimmable electronic ballast. The design approach is described and implemented successfully in a 2×36 W fluorescent lamp system